A thorough theoretical investigation into complexes formed by interaction of dimethyl sulfoxide with two water molecules - Khanh, Pham Ngoc; Viet Nga, Nguyen Thi; Trung, Nguyen Tien (Vietnam Journal of Chemistry, 2017)
A computational study of the stability and the cooperative effect of hydrogen bonds in the complexes of dimethyl sulfoxide and two water molecules was undertaken at the MP2/6-311++G(2d,2p) level of theory. The cooperative energies of obtained complexes are significantly negative, indicating that there is a large cooperativity between types of hydrogen bonds. The existence of the O−H∙∙∙O hydrogen bond present at dimer of water increases the stability of O−H∙∙∙O and C−H∙∙∙O hydrogen bonds in the ternary complexes compared to relevant binary complexes. By vibrational and NBO analyses, it is found that the magnitude of stretching frequency red shift of O−H bonds in the O−H···O hydrogen bonds is enhanced, whereas the extent of stretching frequency blue shift of C−H bonds in the C−H∙∙∙O hydrogen bonds is weakened when the cooperativity of hydrogen bonds happens in the ternary complexes. Obtained results of AIM analysis and stabilization energies indicate the larger contribution of the O−H∙∙∙O relative to the C−H∙∙∙O hydrogen bond to cooperativity. Keywords. Dimethyl sulfoxide, hydrogen bond, cooperativity